2012
DOI: 10.1007/s11205-012-0111-z
|View full text |Cite
|
Sign up to set email alerts
|

Residential Satisfaction in Public Core Housing in Abeokuta, Ogun State, Nigeria

Abstract: This study investigated residential satisfaction of randomly selected 156 household heads in the OGD Workers' housing estate in Abeokuta, Ogun State, Nigeria. Data were collected through questionnaire survey and analysed using descriptive statistics, factor and categorical regression analyses. Respondents were generally satisfied with their housing conditions with 59 % of them expressing satisfaction, while 41 % were neither satisfied nor dissatisfied with their housing environment. They evaluated satisfaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
68
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 83 publications
(79 citation statements)
references
References 35 publications
8
68
0
3
Order By: Relevance
“…Household occupants express their overall housing satisfaction based on objective measures of housing satisfaction (structural components, dwelling units' features, neighbourhood facilities and management services provided by the developers), in line with previous studies (see, e.g. Ibem & Amole, 2012;Jiboye, 2009;Salleh, 2008), as well as subjective measures such as aspirations (the influence of age). Amole (2009) observes that subjective measurement appears to be more relevant housing satisfaction research, thus focusing on age components.…”
Section: Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…Household occupants express their overall housing satisfaction based on objective measures of housing satisfaction (structural components, dwelling units' features, neighbourhood facilities and management services provided by the developers), in line with previous studies (see, e.g. Ibem & Amole, 2012;Jiboye, 2009;Salleh, 2008), as well as subjective measures such as aspirations (the influence of age). Amole (2009) observes that subjective measurement appears to be more relevant housing satisfaction research, thus focusing on age components.…”
Section: Discussionsupporting
confidence: 79%
“…The study affirms the findings of James (2008) that the variation in household housing satisfaction is equally age dependent. Ibem and Amole (2012) have equally found age to predict housing satisfaction in public core housing estate in south-west Nigeria. This has further confirmed that household housing satisfaction relates to changes in age components.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations